The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1423-0410.2009.01188.x
|View full text |Cite
|
Sign up to set email alerts
|

Not every PRP‐gel is born equal Evaluation of growth factor availability for tissues through four PRP‐gel preparations: Fibrinet®, RegenPRP‐Kit®, Plateltex® and one manual procedure

Abstract: Similar methods for platelet gel preparation revealed different performances concerning growth factor recovery and the kinetics of its release from the gel. It is unclear whether these noticeable differences are important for clinical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
185
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(205 citation statements)
references
References 30 publications
(27 reference statements)
13
185
1
4
Order By: Relevance
“…Quantification of growth factor levels and the kinetics of release show similar concentrations of bFGF, VEGF, EGF and TGF-β1 and similar release kinetics with previous published results (Mazzucco et al, 2009). This is particularly remarkable considering that the method used to obtain the conditioned media was different in that the FIBRINET ® kit has been used to produce a matrix gel (Mazzucco et al, 2009) while in our study it has been used to produce a membrane. Further studies are needed to investigate whether the matrix gel and the membrane release growth factors with a similar kinetics.…”
Section: E Lucarelli Et Alsupporting
confidence: 58%
See 1 more Smart Citation
“…Quantification of growth factor levels and the kinetics of release show similar concentrations of bFGF, VEGF, EGF and TGF-β1 and similar release kinetics with previous published results (Mazzucco et al, 2009). This is particularly remarkable considering that the method used to obtain the conditioned media was different in that the FIBRINET ® kit has been used to produce a matrix gel (Mazzucco et al, 2009) while in our study it has been used to produce a membrane. Further studies are needed to investigate whether the matrix gel and the membrane release growth factors with a similar kinetics.…”
Section: E Lucarelli Et Alsupporting
confidence: 58%
“…In addition, blood parametric analysis of the residual serum showed that only 0.9 % of platelets were left in the serum, indicating that 99.1% of the platelets were present in the PRFM (Table 1). Platelet recovery data from PRP obtained with the PRFM FIBRINET ® kit have been previously published from Leitner et al being 65.5% (Leitner et al, 2006;Mazzucco et al, 2009). Considering the platelet concentration factor represented by the PRFM, use of the www.ecmjournal.org E Lucarelli et al A new platelet-rich fibrin matrix PRFM kit produces a 210-fold higher concentration of platelets and fibrin when compared to the initial input whole blood volume.…”
Section: Prfm Descriptionmentioning
confidence: 99%
“…It is logical that if the processing of the sample damages or activates the platelets, the content of its granules would be released prematurely, and as a consequence, would be lost before being used. The study by Mazzucco et al (17) in 2009 further supports this hypothesis. It analyzes four different methods for obtaining platelet-rich plasma.…”
Section: References With Links To Crossref -Doisupporting
confidence: 75%
“…However, there are numerous complex variations among PRP preparation protocols including the starting number of platelets, the use of anticoagulants, the inclusion of leukocytes, and the use of activators [23][24][25][26][27] . The variation in PRP preparation contributes in part to the controversial outcomes both in animal and clinical studies 28 .…”
Section: Discussionmentioning
confidence: 99%